Symbolic courses of cultural objects: collecting, exhibition and the counter metaphor - Luiz Carlos Borges; Marcio D'Olne Campos (Boletim do Museu Paraense Emílio Goeldi. Ciências Humanas, 2012)
Based on concepts related to consumption, productive chain (production context, product, circulation, consumption), and discursivity, we propose to analyze various aspects of the symbolic path an object goes through since its context of production, its musealization until its appropriation by a consumer. In this passage, we deal with some notions such as value of use/value of exchange which refer to different symbolic investments made on objects affiliated to various discursive networks. We focus on different cultural frames present in the management of heritage, with especial regard to the museographic production and presentation of the object towards a consumer, taking into account that, in this kind of cultural production and circulation, several discursive processes of re-signification take place. Thus, what matter are the relations established among a cultural object, the producer, the mediator and the consumer; as well as how the object suffers some discursive modalization when it's re-signified. We assume that musealized object's cultural references are modified throughout the chain that runs from its cultural context of production until the consumer. For the purposes of this analysis, we primarily focus the exhibition "The Mebêngôkre's science: alternatives to destruction", version of 1989, particularly concerning the translation of the Kayapó knowledge system into academic language.